Deification of Technology and the Dignity of the Human Person - Hanes, Pavel; de Muynck, Bram (Communications - Scientific letters of the University of Zilina, 2017)
Technology empowers and enslaves at the same time. Given our proneness to misjudgment and abuse of power, the dangers of technological failure and catastrophe are well known and often discussed. Technological and legislative measures are effective up to a point, but they usually ignore the dignity of the human person that is inalienably related to personal identity, freedom and meaning. So, before we propose new ethical rules we need to make sure they respect the dignity of the human person. The following study chooses the three characteristics of the dignity of the human person as starting points for properly defined ethics. It aims to strengthen ethical awareness and debate in domains where technology becomes confronted with the interests of humanity.